Role of molecular diagnostics in early detection of neonatal sepsis: a narrative review - Madhav Agarwal; Ankur Gupta; Megha Gupta; Surabhi Mahajan; Arti Agrawal; Uday Verma (International Journal of Basic & Clinical Pharmacology, 2026)
Neonatal sepsis is a major cause of illness and death in infants across the globe, particularly in low and middle-income countries. The diagnosis of infections is important in order to provide early treatment to the patient, which may result in improved outcomes. Automated blood culture with antimicrobial susceptibility testing (AST) is considered to be the gold standard, but it has limited clinical utility due to the time required to obtain results, the sensitivity of the method in case of low bacterial loads, and previous antibiotic therapy. The review aims to critically compare the utility of molecular techniques with culture-based techniques in terms of their performance characteristics, like the time required to detect the causative agent, and their clinical utility. The existing literature is in support of the use of molecular techniques in terms of their rapidity and high specificity. Nevertheless, despite their utility, they are not suitable to be used individually, first because they cannot detect phenotypic susceptibility, and second, they may detect non-viable organisms. Therefore, it is important to have a combined approach in order to have a synergistic effect, which may result in improved therapy, enhanced antimicrobial therapy, and improved neonatal health.